2010
DOI: 10.1007/s10554-010-9600-9
|View full text |Cite
|
Sign up to set email alerts
|

Review of Movahed’s sign (D shaped left ventricle seen on gated SPECT) suggestive of right ventricular overload

Abstract: Recently, D shaped ventricle seen on gated SPECT imaging (Movahed's sign) has shown to correlate with right ventricular overload similar to the D shape ventricle seen on echocardiography. Right ventricle (RV) imaging during gated SPECT studies is challenging because of the low tracer uptake due to relatively smaller right ventricular myocardial mass and lower coronary flow to the RV. Increased mass or workload causes higher tracer uptake in the RV wall secondary to increase in RV wall thickness and higher coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Secondly, interventricular septal bowing depends on the cardiac cycle and could be unreliable in a non-ECG gated CT. Whereas RV volume overload produces LV deformity with septal bowing at end diastole, RV pressure overload by pulmonary embolism results in septal bowing throughout the cardiac cycle, [20,21]. However, the degree of septal bowing might be variable according the pressure differences between the RV and LV chambers in the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, interventricular septal bowing depends on the cardiac cycle and could be unreliable in a non-ECG gated CT. Whereas RV volume overload produces LV deformity with septal bowing at end diastole, RV pressure overload by pulmonary embolism results in septal bowing throughout the cardiac cycle, [20,21]. However, the degree of septal bowing might be variable according the pressure differences between the RV and LV chambers in the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although this association between PH and RV abnormalities on SPECT has been observed previously in the literature, our study is the first to link the risk of PH with mortality as a clinical outcome in patients at low risk for coronary artery disease, and suggests a role for SPECT imaging in identifying at-risk patients who might benefit from additional diagnostic evaluation or closer clinical monitoring. 7,13,[24][25][26] Given the frequent and widespread use of SPECT imaging to risk-stratify patients for coronary artery disease, the use of SPECT imaging findings in this fashion could potentially result in earlier diagnosis of pulmonary vascular disease and improved clinical outcomes in a significant number of patients. 27,28 In our study we also observed a significant association with Black race and risk of echocardiographic PH among patients with low-risk SPECT studies.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] In patients with pre-existing coronary artery disease or pulmonary vascular disease, the presence of RV abnormalities on SPECT imaging (including dilation and hypertrophy) have been associated with both disease severity and increased mortality, and may have prognostic significance. 7,[10][11][12][13] However, in patients without known coronary artery disease (as confirmed by low-risk or negative SPECT imaging studies), who do not have existing pulmonary vascular disease, the significance of incidentally observed RV abnormalities has not been defined. This scenario leads to a conundrum for the referring physician in determining the clinical implications of this finding, and what, if any, follow-up is needed for a patient with a low-risk study but evidence of RV abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 6 ] In fact, most information about this anatomical finding in myocardial scintigraphy is limited to isolated reports and small case series. [ 7 8 ] In an observational retrospective report, Movahed et al . found that “D-shaped” LV in SPECT imaging correlated well with right ventricle overload; a history of ASD was found in 38% of this sample.…”
Section: Discussionmentioning
confidence: 99%